Resist material, resist film, and pattern forming method

A polymer-based resist material with specific structural units addresses the challenge of forming precise semiconductor patterns by enhancing sensitivity and resolution, enabling efficient low-dose pattern formation.

JP7604836B2Active Publication Date: 2024-12-24OJI HLDG CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020174042
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-15
Publication Date
2024-12-24
Estimated Expiration
2040-10-15

AI Technical Summary

Technical Problem

Existing lithography methods face challenges in forming highly sensitive resist films for precise and fine semiconductor device patterns, necessitating the development of advanced resist materials with improved sensitivity and resolution.

Method used

A resist material comprising a polymer with specific structural units derived from general formulas (101) and (104) is used, which enhances sensitivity and allows pattern formation with reduced electromagnetic radiation doses, leading to high-definition patterning.

Benefits of technology

The resist material enables the formation of highly sensitive resist films that can form precise patterns even with low radiation doses, improving efficiency and resolution in semiconductor manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604836000045
    Figure 0007604836000045
  • Figure 0007604836000001
    Figure 0007604836000001
  • Figure 0007604836000002
    Figure 0007604836000002
Patent Text Reader

Abstract

To provide a resist material capable of forming a highly sensitive resist film.SOLUTION: The present invention relates to the resist material containing a polymer which contains a unit derived from a structure represented by general formula (101) and a unit derived from a structure represented by general formula (104). The resist material of the present invention may further have a unit derived from a structure represented by general formula (102) and / or a unit derived from a structure represented by general formula (103).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resist material, a resist film, and a pattern forming method. [Background technology]

[0002] Electronic devices such as semiconductors are required to have higher definition through miniaturization. In addition, diversification of shapes of semiconductor device patterns is also being considered. As a method for forming such a pattern, for example, a lithography method using a photoresist is known. In the lithography method using a photoresist, a resist film is formed on a semiconductor substrate such as a silicon wafer, and the resist film is irradiated with electromagnetic waves such as ultraviolet rays through a photomask on which a semiconductor device pattern is drawn, and developed, and the substrate is etched using the photoresist pattern obtained as a protective film, whereby fine irregularities corresponding to the pattern can be formed on the substrate.

[0003] As the resist material constituting the resist film, polymers having various structures are used according to the purpose and the required physical properties. For example, as the polymer used in the resist material, a polymer containing a structural unit derived from (meth)acrylate is known. In Patent Documents 1 to 3, the use of a polymer obtained by copolymerizing α-methylstyrene with methacrylic acid or a methacrylic acid ester as the resist material is considered.

[0004] In addition, Patent Document 4 considers using a polymer obtained by polymerizing an adamantyl methacrylate monomer and a t-butyl acrylate monomer as a radiation-sensitive material. In this way, two specific monomer components are copolymerized to form a resist material, and a resist film is formed. Patent Document 5 discloses a resist material using an acrylic ester resin containing a fluorinated alkyl group in the ester side chain as a base polymer. The resist material in Patent Document 5 is a chemically amplified resist material used together with a photoacid generator and a basic compound. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 117243 / 1983 [Patent Document 2] Japanese Patent Application Laid-Open No. 63-137227 [Patent Document 3] International Publication No. WO99 / 62964 [Patent Document 4] Japanese Patent Application Publication No. 07-234511 [Patent Document 5] JP 2002-155118 A Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, in the lithography method using a photoresist, the formation of a fine pattern is being considered. In order to form a fine pattern, it is necessary to pattern a resist film with high precision, and therefore, the development of a highly sensitive resist material is required.

[0007] Therefore, in order to solve such problems of the conventional techniques, the present inventors have carried out studies with the aim of providing a resist material capable of forming a highly sensitive resist film. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above problems, the present inventors have found that a highly sensitive resist film can be formed by using a monomer having a predetermined structure as a polymerization component of a polymer that constitutes a resist material. Specifically, the present invention has the following configuration.

[0009] [1] A resist material containing a polymer including a unit derived from a structure represented by the following general formula (101) and a unit derived from a structure represented by the following general formula (104): [ka] [ka] In general formula (101), R 1 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted acyl group, an optionally substituted allyl group, an optionally substituted alkoxy group, or an optionally substituted alkylsilyl group, 1 may be the same or different; R 11 represents a hydrogen atom or an alkyl group which may have a substituent; R 2 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 1 represents a single bond or a linking group; In general formula (104), X 3 represents a halogenated alkyl group, R 5 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 4 represents a single bond or a linking group. [2] The resist material according to [1], wherein the polymer further contains a unit derived from a structure represented by the following general formula (102): [ka] In general formula (102), X 1 represents an optionally substituted alkyl group (excluding those containing a halogen atom as a substituent), an optionally substituted acyl group, or an optionally substituted allyl group; R 3 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 2 represents a single bond or a linking group. [3] The resist material according to [1] or [2], wherein the polymer further contains a unit derived from a structure represented by the following general formula (103): [ka] In general formula (103), X 2 represents an optionally substituted aryl group; R 4 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 3 represents a single bond or a linking group. [4] The resist material according to any one of [1] to [3], wherein the content of units derived from the structure represented by general formula (104) in the polymer is 1 to 40 mol %. [5] In the general formula (101), R 2 is a fluorine atom, a chlorine atom or a bromine atom. [6] In the general formula (101), R 11 The resist material according to any one of [1] to [5], wherein [7] In the general formula (102), R 3 is a fluorine atom, a chlorine atom or a bromine atom. [8] A resist film formed from the resist material according to any one of [1] to [7]. [9] A step of applying the resist material according to any one of [1] to [7] onto a substrate to form a resist film; An exposure process; A developing step.

[10] The pattern forming method according to [9], further comprising a metal introduction step prior to the development step.

[11] The pattern forming method according to [9] or

[10] , wherein in the exposure step, the resist film is irradiated with electromagnetic waves having a wavelength of 15 nm or less.

[12] The pattern formation method according to any one of [9] to

[11] , wherein the developer used in the development step contains at least one compound selected from the group consisting of an ester-based compound, a ketone-based compound, and an alcohol-based compound. Effect of the Invention

[0010] According to the present invention, a resist material capable of forming a highly sensitive resist film can be obtained. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view illustrating the configuration of a substrate and a resist film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits.

[0013] (Resist material) The present invention relates to a resist material containing a polymer including a unit derived from a structure represented by the following general formula (101) and a unit derived from a structure represented by the following general formula (104). [ka] [ka]

[0014] In general formula (101), R 1 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted acyl group, an optionally substituted allyl group, an optionally substituted alkoxy group, or an optionally substituted alkylsilyl group, 1 may be the same or different. 11 R represents a hydrogen atom or an alkyl group which may have a substituent. 2 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 1 represents a single bond or a linking group.

[0015] In addition, in the general formula (104), X 3 represents a halogenated alkyl group, R 5 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 4 represents a single bond or a linking group.

[0016] The resist material of the present invention can form a highly sensitive resist film by containing a polymer containing a unit derived from the above structure. Specifically, even if the amount of electromagnetic radiation (dose) per unit area irradiated to the resist film formed from the resist material is small, a pattern of a desired shape can be formed. For example, in the resist material of this embodiment, the dose during electron beam irradiation is 160 μC / cm. 2 or less, or even when the dose is 60 μC / cm 2 Less than 45μC / cm 2 In the case of a highly sensitive resist film, the irradiation intensity of the electron beam can be weakened and the irradiation time can be shortened, so that the efficiency of the patterning process can be improved.

[0017] Furthermore, the resist material of this embodiment contains a polymer containing a unit derived from the above structure, so that a resist film capable of high-definition patterning can be formed. That is, the resist film formed from the resist material of this embodiment has high resolution. For example, even in a line-and-space line pattern with a narrow line width, if the line is linear and there is no residue derived from the resist film in the space portion, the resist film can be evaluated as having high resolution. That is, when the resolution of the resist film is high, a pattern with high resolution and a desired shape can be formed.

[0018] The amount of the polymer is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the total mass of the resist material, and is preferably 40% by mass or less, and more preferably 30% by mass or less, based on the total mass of the resist material.

[0019] The resist film formed from the resist material of this embodiment is, for example, a film (protective film) provided on a substrate such as a silicon wafer in order to form a pattern on the substrate. The resist film may be a film provided so as to be in direct contact with the substrate, or may be a film laminated on the substrate via another layer. The resist film is processed into a pattern shape to be formed on the substrate, and the portion remaining as the pattern shape becomes a protective film in the subsequent etching process. After the pattern is formed on the substrate, the resist film (protective film) may be removed from the substrate. In this way, the resist film is used, for example, in the process of forming a pattern on the substrate.

[0020] The resist material of this embodiment is preferably a main chain scission type positive resist material. When the polymer contained in the resist material is irradiated with electromagnetic rays, the main chain is scissed, and only the exposed portion dissolves in the developer. This makes it possible to form a more fine pattern.

[0021] <Polymer> The resist material of this embodiment contains a polymer containing a unit derived from a structure represented by the following general formula (101) and a unit derived from a structure represented by the following general formula (104). That is, the polymer preferably contains at least a unit derived from a sugar derivative and a unit having a halogenated alkyl group. In this specification, a "unit" refers to a repeating unit (monomer unit) constituting the main chain of the polymer. However, a unit derived from one sugar derivative may further contain a unit derived from a sugar derivative in the side chain, in which case the repeating unit (monomer unit) constituting the side chain polymer also corresponds to a "unit" as used herein. [ka] [ka]

[0022] In general formula (101), R 1 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted acyl group, an optionally substituted allyl group, an optionally substituted alkoxy group, or an optionally substituted alkylsilyl group, 1 may be the same or different. 11 R represents a hydrogen atom or an alkyl group which may have a substituent. 2 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 1 represents a single bond or a linking group.

[0023] In addition, in the general formula (104), X 3 represents a halogenated alkyl group, R 5 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 4 represents a single bond or a linking group.

[0024] In general formula (101), R 1 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted acyl group, an optionally substituted allyl group, an optionally substituted alkoxy group, or an optionally substituted alkylsilyl group. Here, the optionally substituted alkyl group includes a sugar derivative group, and R 1 may be a unit derived from a linear or branched chain sugar derivative. The unit derived from a linear or branched chain sugar derivative is preferably a sugar derivative having the same structure as the sugar derivative to which it is bound. 1 is a unit derived from a linear or branched sugar derivative, the number of linked sugar derivative groups (average degree of polymerization of the sugar derivative) is preferably 20 or less, more preferably 10 or less.

[0025] Among them, R 1 are each preferably independently a hydrogen atom, an optionally substituted alkyl group, or an optionally substituted acyl group, and R 1 R is preferably a hydrogen atom or an acyl group which may have a substituent, and more preferably an acyl group which may have a substituent. 1 When is an optionally substituted acyl group, the sensitivity of the resist material can be increased more effectively.

[0026] R 1 When is an alkyl group or an acyl group, the number of carbon atoms can be appropriately selected depending on the purpose. For example, the number of carbon atoms is preferably 1 or more, and is preferably 200 or less, more preferably 100 or less, even more preferably 20 or less, and particularly preferably 4 or less.

[0027] R 1 Specific examples of R include acyl groups such as acetyl, propanoyl, butyryl, isobutyryl, valeryl, isovaleryl, pivaloyl, hexanoyl, octanoyl, chloroacetyl, trichloroacetyl, trifluoroacetyl, cyclopentanecarbonyl, cyclohexanecarbonyl, benzoyl, methoxybenzoyl, trifluoromethoxybenzoyl, and chlorobenzoyl; and alkyl groups such as methyl, ethyl, n-propyl, n-butyl, i-butyl, and t-butyl. 1 is preferably a methyl group, an ethyl group, an acetyl group, a trifluoroacetyl group, a propanoyl group, an n-butyryl group, an isobutyryl group, a benzoyl group, or a trimethylsilyl group, and particularly preferably an acetyl group, a propanoyl group, or a trifluoroacetyl group.

[0028] In general formula (101), R 11 R represents a hydrogen atom or an alkyl group which may have a substituent. 11When R represents an alkyl group which may have a substituent, examples of the alkyl group include a methyl group, an ethyl group, a propyl group, etc. Among these, the alkyl group is preferably a methyl group, and such an alkyl group preferably further has a substituent. Examples of the substituent that the alkyl group has include a hydroxyl group, an acyl group, an allyl group, an alkoxy group, etc. Among these, the substituent is preferably a hydroxyl group or an acyl group. More specifically, R 11 When R represents an alkyl group which may have a substituent, 11 -CH2OR 1 Preferably, R 1 The above-mentioned groups can be mentioned as examples of R 11 It is particularly preferred that R is a hydrogen atom. 11 By making the atom a hydrogen atom, it becomes easier to form a finer pattern structure.

[0029] In general formula (101), R 2 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom, or a halogenated alkyl group. 2 R is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluorine atom, a chlorine atom or a bromine atom, and particularly preferably a fluorine atom, a chlorine atom or a bromine atom. 2 By introducing fluorine, chlorine or bromine atoms into the compound, the resist film formed can be made more sensitive.

[0030] In general formula (101), Y 1 Each independently represents a single bond or a linking group. Y 1 When is a linking group, Y 1 Examples of Y include linking groups that do not contain a sugar unit, such as groups containing an alkylene group, a phenylene group, -O-, -C(=O)O-, etc. 1 may be a linking group combining these groups. 1 is preferably a linking group represented by the following structural formula: [ka]

[0031] In the above structural formula, the * symbol indicates the bonding site with the main chain, and the * symbol indicates the bonding site with the sugar unit of the side chain.

[0032] In the above general formula (101), the structure of the sugar derivative is described as a cyclic structure, but the structure of the sugar derivative may be not only a cyclic structure but also an open-ring structure (chain structure) called an aldose or ketose.

[0033] The resist material of this embodiment contains the structure of the sugar derivative represented by the general formula (101) above, and is therefore useful as a main chain scission type positive resist material. In general, in main chain scission type resists, it is said that radicals are generated in the polymer by the irradiated light energy, and the main chain is scissed. However, in conventional main chain scission type resists, even if radicals are generated, the radicals disappear afterwards, so the efficiency of main chain scission is poor, and therefore the sensitivity is low. On the other hand, in the resist material of this embodiment, the number of radical generation sites is increased by having a sugar chain with many CO bonds, and the frequency of radical generation increases even with low light energy per unit area, so that main chain scission can be further promoted. It is believed that this improves the sensitivity of the resist material.

[0034] In general formula (104), X 3 represents a halogenated alkyl group. 3The number of carbon atoms in the halogenated alkyl group represented by is preferably 1 to 10, more preferably 1 to 5, and even more preferably 1 to 3. The halogenated alkyl group is preferably a fluoroalkyl group, a chloroalkyl group, or a bromoalkyl group, more preferably a fluoroalkyl group or a chloroalkyl group, and particularly preferably a fluoroalkyl group. Examples of the halogenated alkyl group include a difluoroalkyl group, a trichloroalkyl group, a perfluoroalkyl group, a trifluoroalkyl group, a tetrafluoroalkyl group, a heptafluoroalkyl group, a hexafluoroalkyl group, and a hexachloroalkyl group.

[0035] In general formula (104), R 5 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom, or a halogenated alkyl group. 5 is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluorine atom, a chlorine atom or a bromine atom, and particularly preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms.

[0036] In general formula (104), Y 4 represents a single bond or a linking group. 4 When is a linking group, Y 4 Examples of Y include linking groups that do not contain a sugar unit, such as groups containing an alkylene group, a phenylene group, -O-, -C(=O)O-, etc. 4 Y may be a linking group combining these groups. 4 As the group, Y in the general formula (101) is 1 The examples of the groups include those having the same structures as those of the groups which may be taken by the formula (I).

[0037] The content (mol%) of the unit derived from the structure represented by general formula (101) is preferably 0.5 mol% to 95 mol% based on the total mass of the polymer, more preferably 1 mol% to 90 mol%, even more preferably 2 mol% to 85 mol%, and particularly preferably 5 mol% to 75 mol%. By setting the content of the unit derived from the structure represented by general formula (101) within the above range, the sensitivity of the resist film formed from the resist material can be more effectively increased.

[0038] The content (mass%) of the unit derived from the structure represented by general formula (104) is preferably 0.3 mol% to 40 mol%, more preferably 0.5 mol% to 30 mol%, even more preferably 0.7 mol% to 20 mol%, and particularly preferably 1 mol% to 10 mol%. By setting the content of the unit derived from the structure represented by general formula (104) within the above range, the sensitivity of the resist film formed from the resist material can be more effectively increased.

[0039] The content of the unit derived from the structure represented by the general formula (101) and the content of the unit derived from the structure represented by the general formula (104) are, for example, 1 The molar composition ratio can be determined from the H-NMR signal integral ratio.

[0040] The polymer contained in the resist material of this embodiment preferably further contains a unit derived from a structure represented by general formula (102) below. [ka] General formula (102)

[0041] In general formula (102), X 1 R represents an alkyl group which may have a substituent (excluding those containing a halogen atom as a substituent), an acyl group which may have a substituent, or an allyl group which may have a substituent. 3represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 2 represents a single bond or a linking group.

[0042] In general formula (102), X 1 represents an alkyl group which may have a substituent (excluding those containing a halogen atom as a substituent), an acyl group which may have a substituent, or an allyl group which may have a substituent. 1 is preferably an alkyl group which may have a substituent (excluding those containing a halogen atom in the substituent), and particularly preferably an alkyl group which has no substituent. The number of carbon atoms in the alkyl group is preferably 1 to 8, more preferably 1 to 5, and even more preferably 1 to 3. The above carbon number is the number of carbon atoms excluding the number of carbon atoms in the substituent. Examples of the alkyl group having a substituent include, for example, -CH2-OH, -CH2-O-methyl, -CH2-O-ethyl, -CH2-On-propyl, -CH2-O-isopropyl, -CH2-On-butyl, -CH2-O-isobutyl, -CH2-Ot-butyl, -CH2-O-(C=O)-methyl, -CH2-O-(C=O)-ethyl, -CH2-O-(C=O)-propyl, -CH2-O-(C=O)-isopropyl, -CH2-O-(C=O)-n-butyl, -CH2-O-(C=O)-isobutyl, -CH2-O-(C=O)-t-butyl, -C2H4-OH, -C2H4-O -methyl, -C2H4-O-ethyl, -C2H4-On-propyl, -C2H4-O-isopropyl, -C2H4-On-butyl, -C2H4-O-isobutyl, -C2H4-Ot-butyl, -C2H4-O-(C=O)-methyl, -C2H4-O-(C=O)-ethyl, -C2H4-O-(C=O)-n-propyl, -C2H4-O-(C=O)-isopropyl, -C2H4-O-(C=O)-n-butyl, -C2H4-O-(C=O)-isobutyl, -C2H4-O-(C=O)-t-butyl, -C2H4-O-(C=O)-CH2-(C=O)-methyl, etc. The alkyl group having a substituent may be a cycloalkyl group.

[0043] In general formula (102), R 3 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom, or a halogenated alkyl group. 3 R is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluorine atom, a chlorine atom or a bromine atom, and particularly preferably a fluorine atom, a chlorine atom or a bromine atom. 3 By introducing a fluorine atom, a chlorine atom, or a bromine atom into the R in the general formula (101), the sensitivity of the formed resist film can be improved. 2 and R in general formula (102) 3 At least one of R in the general formula (101) is preferably a fluorine atom, a chlorine atom, or a bromine atom. 2 and R in general formula (102) 3 may both be fluorine atoms, chlorine atoms or bromine atoms.

[0044] In general formula (102), Y 2 represents a single bond or a linking group. 2 When is a linking group, Y 2 Examples of Y include groups containing an alkylene group, a phenylene group, -O-, -C(=O)O-, etc. 2 may be a linking group combining these groups. 2 is preferably a linking group represented by the following structural formula: [ka]

[0045] In the above structural formula, the mark * indicates the bonding site with the main chain, and the mark * indicates X 1 It represents the binding site with

[0046] When the polymer contains a unit derived from the structure represented by general formula (102), the content (mol%) of the unit derived from the structure represented by general formula (102) is preferably 0.5 mol% to 99 mol%, more preferably 3 mol% to 98 mol%, and particularly preferably 10 mol% to 95 mol% based on the total mass of the polymer. The content (mol%) of the unit derived from the structure represented by general formula (102) can be calculated in the same manner as the calculation of the content of the unit derived from the structure represented by general formula (101) described above.

[0047] The polymer contained in the resist material of this embodiment preferably further contains a unit derived from a structure represented by the following general formula (103): When the polymer further contains a unit derived from a structure represented by general formula (103), the solubility in organic solvents can be improved. [ka]

[0048] In general formula (103), X 2 R represents an aryl group which may have a substituent. 4 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 3 represents a single bond or a linking group.

[0049] In general formula (103), X 2 represents an aryl group which may have a substituent. 2 is preferably a phenyl group.

[0050] In general formula (103), R 4 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom, or a halogenated alkyl group. 4 R is preferably a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a fluorine atom, a chlorine atom or a bromine atom, and particularly preferably a fluorine atom, a chlorine atom or a bromine atom. 4By introducing fluorine, chlorine or bromine atoms into the compound, the resist film formed can be made more sensitive.

[0051] In general formula (103), Y 3 represents a single bond or a linking group. 2 When is a linking group, Y 3 Examples of Y include groups containing an alkylene group, a phenylene group, -O-, -C(=O)O-, etc. 3 may be a linking group that is a combination of these groups. 3 is particularly preferably a single bond.

[0052] The unit derived from the structure represented by the general formula (103) is preferably a unit derived from a styrene compound. Examples of the styrene compound include styrene, o-methylstyrene, p-methylstyrene, ethylstyrene, p-methoxystyrene, p-phenylstyrene, 2,4-dimethylstyrene, pn-octylstyrene, pn-decylstyrene, pn-dodecylstyrene, chlorostyrene, bromostyrene, trimethylsilylstyrene, hydroxystyrene, 3,4,5-methoxystyrene, pentamethyldisilylstyrene, t-butoxycarbonylstyrene, tetrahydropyranylstyrene, phenoxyethylstyrene, and t-butoxycarbonylmethylstyrene.

[0053] When the polymer contains a unit derived from the structure represented by general formula (103), the content (mol%) of the unit derived from the structure represented by general formula (103) is preferably 0.5 mol% to 98 mol%, more preferably 2 mol% to 97 mol%, and particularly preferably 10 mol% to 95 mol% based on the total mass of the polymer. The content (mass%) of the unit derived from the structure represented by general formula (103) can be calculated in the same manner as the calculation of the content of the unit derived from the structure represented by general formula (101) described above.

[0054] The polymer contained in the resist material of this embodiment preferably contains units derived from the structures represented by the above-mentioned general formula (101) and general formula (104), and further contains units derived from the structures represented by general formula (102) and / or (103). Thus, the polymer contained in the resist material of this embodiment is a copolymer, and the copolymer may be a block copolymer or a random copolymer. Also, the copolymer may have a structure in which a part is a random copolymer and a part is a block copolymer. In this way, an appropriate structure can be selected depending on the application and required physical properties. However, since the radical generating sites are dispersed in the polymer, the resist has high resolution and can form a fine pattern, so that the copolymer is preferably a random copolymer.

[0055] The weight average molecular weight (Mw) of the polymer is preferably 5000 or more, more preferably 8000 or more, and even more preferably 10000 or more. The weight average molecular weight (Mw) of the polymer is preferably 2 million or less, more preferably 1.5 million or less, even more preferably 1 million or less, and even more preferably 700,000 or less. The weight average molecular weight (Mw) of the polymer is a value measured in terms of polystyrene by GPC.

[0056] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the polymer is preferably at least 1. Moreover, Mw / Mn is preferably at most 100, more preferably at most 50, even more preferably at most 20, still more preferably at most 15, and particularly preferably at most 10.

[0057] The solubility of the polymer in at least one selected from PGMEA, PGME, THF, butyl acetate, anisole, cyclohexanone, ethyl lactate, N-methylpyrrolidone, γ-butyrolactone and DMF is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 3% by mass or more, and more particularly preferably 4% by mass or more. The upper limit of the solubility of the polymer in the organic solvent is not particularly limited, but can be, for example, 40% by mass. The solubility is the solubility in at least one selected from PGMEA, PGME, THF, butyl acetate, anisole, cyclohexanone, ethyl lactate, N-methylpyrrolidone, γ-butyrolactone and DMF.

[0058] The solubility of a polymer is measured by gradually adding PGMEA, PGME, THF, butyl acetate, anisole, cyclohexanone, ethyl lactate, N-methylpyrrolidone, γ-butyrolactone or DMF to a given amount of polymer while stirring, and recording the amount of organic solvent added when the polymer is dissolved. A magnetic stirrer or the like may be used for stirring. The solubility is then calculated from the following formula. Solubility (mass%) = polymer mass / (polymer mass + organic solvent mass) x 100

[0059] <Polymer synthesis method> The synthesis of the polymer can be carried out by known polymerization methods such as living radical polymerization, living anionic polymerization, and atom transfer radical polymerization. For example, in the case of living radical polymerization, a copolymer can be obtained by reacting a monomer with a polymerization initiator such as AIBN (α,α'-azobisisobutyronitrile). In the case of living anionic polymerization, a polymer can be obtained by reacting a monomer with butyllithium in the presence of lithium chloride. Note that, although an example of polymer synthesis is shown in this example, the present embodiment is not limited thereto, and the polymer can be appropriately synthesized by each of the above synthesis methods or known synthesis methods. For example, the method described in International Publication WO99 / 062964 and the like can be used.

[0060] In addition, when synthesizing a polymer, a step of extracting from lignocellulose derived from woody plants or herbaceous plants may be combined. For example, when a method of extracting from lignocellulose derived from woody plants or herbaceous plants is adopted, the extraction method described in JP 2012-100546 A or the like can be used.

[0061] Xylan can be extracted, for example, by the method disclosed in JP-A-2012-180424.

[0062] When synthesizing a polymer, it is preferable to use the OH group of the sugar moiety obtained by the above extraction method after modifying it by esterification, etc. For example, when an acetyl group is introduced, an acetylated sugar derivative moiety can be obtained by reacting it with acetic anhydride.

[0063] When synthesizing copolymers, Macromolecules Vol.36, No.6, 2003 can be used as a reference. Specifically, each compound is placed in a solvent containing DMF, water, acetonitrile, etc., and a reducing agent is added. Examples of reducing agents include NaCNBH3. The mixture is then stirred at 30°C to 100°C for 1 day to 20 days, and reducing agent is added as necessary. A precipitate is obtained by adding water, and the solids are vacuum dried to obtain the copolymer.

[0064] In addition to the above-mentioned methods, examples of the copolymer synthesis method include synthesis methods using radical polymerization, RAFT polymerization, ATRP polymerization, click reaction, and NMP polymerization. Radical polymerization is a polymerization reaction that occurs by adding an initiator and generating two free radicals through a thermal or photoreaction. By heating a monomer (e.g., a styrene monomer and a sugar methacrylate compound in which methacrylic acid is added to the β-1 position at the terminal of a xylooligosaccharide) and an initiator (e.g., an azo compound such as azobisbutyronitrile (AIBN)) at 150°C, a polystyrene-polysaccharide methacrylate random copolymer can be synthesized. RAFT polymerization is a radical-initiated polymerization reaction that involves an exchange chain reaction using thiocarbonylthio groups. For example, the OH group at the terminal 1 position of xylooligosaccharides can be converted to a thiocarbonylthio group, and then styrene monomer can be reacted at 30°C to 100°C to synthesize a copolymer (Material Matters vol.5, No.1, Latest Polymer Synthesis, Sigma-Aldrich Japan Co., Ltd.). In ATRP polymerization, the terminal OH group of a sugar is halogenated, and then reacted with a metal complex [(CuCl, CuCl2, CuBr, CuBr2, CuI, etc.) + TPMA (tris(2-pyridylmethyl)amine)], MeTREN (tris[2-(dimethylamino)ethyl]amine), etc.), a monomer (e.g., styrene monomer), and a polymerization initiator (2,2,5-trimethyl-3-(1-phenylethoxy)-4-phenyl-3-azahexane) to synthesize a sugar copolymer (e.g., a sugar-styrene block copolymer). In NMP polymerization, an alkoxyamine derivative is used as an initiator and heated to couple with monomer molecules and produce nitroxides. The polymerization reaction then proceeds as radicals are generated by thermal dissociation. This type of NMP polymerization is a type of living radical polymerization reaction. By mixing monomers (for example, styrene monomers and sugar methacrylate compounds in which methacrylic acid is added to the β-1 position at the end of xylooligosaccharides), using 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO) as an initiator, and heating at 140°C, a polystyrene-polysaccharide methacrylate random copolymer can be synthesized. The click reaction is a Cu-catalyzed 1,3-dipolar azide / alkyne cycloaddition reaction of propargyl-containing sugars.

[0065] <Organic solvent> The resist material of the present embodiment may further contain an organic solvent. However, the resist material may further contain an aqueous solvent such as water or various aqueous solutions in addition to the organic solvent. Examples of the organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, sulfur-containing solvents, amide-based solvents, ester-based solvents, and hydrocarbon-based solvents. These solvents may be used alone or in combination of two or more.

[0066] Examples of alcohol-based solvents include methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, sec-butanol, tert-butanol, n-pentanol, i-pentanol, 2-methylbutanol, sec-pentanol, tert-pentanol, 3-methoxybutanol, n-hexanol, 2-methylpentanol, sec-hexanol, 2-ethylbutanol, sec-heptanol, 3-heptanol, n-octanol, 2-ethylhexanol, sec-octanol, n-nonyl alcohol, 2,6-dimethyl-4-heptanol, n-decanol, sec-undecyl alcohol, trimethylnonyl alcohol, sec-tetradecyl alcohol, sec- Examples of the alcohol include heptadecyl alcohol, furfuryl alcohol, phenol, cyclohexanol, methylcyclohexanol, 3,3,5-trimethylcyclohexanol, benzyl alcohol, and diacetone alcohol; ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, 1H,1H-trifluoroethanol, 1H,1H-pentafluoropropanol, and 6-(perfluoroethyl)hexanol.

[0067] Examples of polyhydric alcohol partial ether solvents include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monohexyl ether, ethylene glycol monophenyl ether, ethylene glycol mono-2-ethylbutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monohexyl ether, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, and dipropylene glycol monopropyl ether.

[0068] Examples of ether solvents include diethyl ether, dipropyl ether, dibutyl ether, diphenyl ether, and tetrahydrofuran (THF).

[0069] Examples of ketone solvents include acetone, methyl ethyl ketone, methyl-n-propyl ketone, methyl-n-butyl ketone, diethyl ketone, methyl-i-butyl ketone, methyl-n-pentyl ketone, methyl-i-pentyl ketone, ethyl-n-butyl ketone, methyl-n-hexyl ketone, di-i-butyl ketone, trimethylnonanone, cyclopentanone, cyclohexanone, cycloheptanone, cyclooctanone, methylcyclohexanone, 2,4-pentanedione, acetonylacetone, acetophenone, and furfural.

[0070] An example of the sulfur-containing solvent is dimethyl sulfoxide.

[0071] Examples of amide solvents include N,N'-dimethylimidazolidinone, N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropionamide, and N-methylpyrrolidone.

[0072] Examples of ester-based solvents include diethyl carbonate, propylene carbonate, methyl acetate, ethyl acetate, γ-butyrolactone, γ-valerolactone, n-propyl acetate, i-propyl acetate, n-butyl acetate, i-butyl acetate, sec-butyl acetate, n-pentyl acetate, sec-pentyl acetate, 3-methoxybutyl acetate, methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, benzyl acetate, cyclohexyl acetate, methylcyclohexyl acetate, n-nonyl acetate, methyl acetoacetate, ethyl acetoacetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, Examples of the monomer include diethylene glycol mono-n-butyl ether acetate, propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, glycol diacetate, methoxytriglycol acetate, ethyl propionate, n-butyl propionate, i-amyl propionate, methyl 3-methoxypropionate, diethyl oxalate, di-n-butyl oxalate, methyl lactate, ethyl lactate, n-butyl lactate, n-amyl lactate, diethyl malonate, dimethyl phthalate, and diethyl phthalate.

[0073] Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents such as n-pentane, i-pentane, n-hexane, i-hexane, n-heptane, i-heptane, 2,2,4-trimethylpentane, n-octane, i-octane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, mesitylene, ethylbenzene, trimethylbenzene, methylethylbenzene, n-propylbenzene, i-propylbenzene, diethylbenzene, i-butylbenzene, triethylbenzene, di-i-propylbenzene, n-amylnaphthalene, and anisole.

[0074] Among these, the organic solvent is more preferably propylene glycol monomethyl ether acetate (PGMEA), N,N-dimethylformamide (DMF), propylene glycol monomethyl ether (PGME), anisole, ethanol, methanol, acetone, methyl ethyl ketone, hexane, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), 1H,1H-trifluoroethanol, 1H,1H-pentafluoropropanol, 6-(perfluoroethyl)hexanol, ethyl acetate, propyl acetate, butyl acetate, cyclohexanone, furfural, N-methylpyrrolidone, or γ-butyrolactone, and even more preferably PGMEA, PGME, THF, butyl acetate, anisole, cyclohexanone, N-methylpyrrolidone, γ-butyrolactone, or DMF, and even more preferably anisole, PGME, or PGMEA. These solvents may be used alone or in combination of two or more.

[0075] The content of the organic solvent is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the total mass of the resist material. The content of the organic solvent is preferably 99.9% by mass or less, and more preferably 99% by mass or less. By setting the content of the organic solvent within the above range, the coatability of the resist material can be improved.

[0076] <Optional ingredients> The resist material of this embodiment may contain optional components as described below.

[0077] <<Monomer components>> The resist material of this embodiment may further contain a monomer component constituting the polymer in addition to the polymer. Examples of the monomer component include the above-mentioned compounds represented by general formula (101) or general formula (104), and compounds represented by general formula (102) or (103).

[0078] <<Crosslinkable compound>> The resist material of this embodiment may further contain a crosslinking compound. This crosslinking reaction makes the formed resist film stronger, and can increase the etching resistance. In addition, when a crosslinking compound is added, the crosslinking reaction of the polymer in the exposed area can be promoted and insolubilized by irradiating it with electromagnetic waves. In this case, the resist film (resist material) in the unexposed area can be removed by treating it with an appropriate developer.

[0079] The crosslinkable compound is not particularly limited, but a crosslinkable compound having at least two crosslink-forming substituents is preferably used. A compound having at least one type of crosslink-forming substituent selected from an isocyanate group, an epoxy group, a hydroxymethylamino group, and an alkoxymethylamino group, two or more, for example, 2 to 6, can be used as the crosslinkable compound. Only one type of crosslinkable compound can be used, or two or more types of compounds can be used in combination.

[0080] These crosslinking compounds can undergo a crosslinking reaction by self-condensation, or can undergo a crosslinking reaction with a structural unit contained in a polymer.

[0081] <<Catalyst>> To the resist material, as a catalyst for promoting the crosslinking reaction, an acid compound such as p-toluenesulfonic acid, trifluoromethanesulfonic acid, pyridinium-p-toluenesulfonic acid, salicylic acid, sulfosalicylic acid, citric acid, benzoic acid, ammonium dodecylbenzenesulfonate, hydroxybenzoic acid, etc. can be added. In addition, as a catalyst, an acid generator such as 2,4,4,6-tetrabromocyclohexadienone, benzoin tosylate, 2-nitrobenzyl tosylate, bis(4-tert-butylphenyl)iodonium trifluoromethanesulfonate, triphenylsulfonium trifluoromethanesulfonate, phenyl-bis(trichloromethyl)-s-triazine, N-hydroxysuccinimide trifluoromethanesulfonate, etc. can be added.

[0082] <<Anti-reflection agent>> The resist material of this embodiment may further include a light-reflection preventing agent. Examples of light-reflection preventing agents include compounds having light-absorbing properties. Examples of light-absorbing compounds include those having high absorption ability for light in the photosensitive characteristic wavelength region of the photosensitive component in the photoresist provided on the light-reflection preventing film, such as benzophenone compounds, benzotriazole compounds, azo compounds, naphthalene compounds, anthracene compounds, anthraquinone compounds, and triazine compounds. Examples of polymers include polyesters, polyimides, polystyrenes, novolac resins, polyacetals, and acrylic polymers. Examples of polymers having light-absorbing groups linked by chemical bonds include polymers having light-absorbing aromatic ring structures such as anthracene rings, naphthalene rings, benzene rings, quinoline rings, quinoxaline rings, and thiazole rings.

[0083] <<Other Ingredients>> The resist material may further contain an ionic liquid, a surfactant, etc. By including an ionic liquid in the resist material, the compatibility between the polymer and the organic solvent can be increased. The resist material can be made to contain a surfactant to improve the applicability of the resist material to a substrate. Preferred surfactants include nonionic surfactants, fluorine-based surfactants, and silicon-based surfactants. In addition, any other materials such as known rheology modifiers, adhesion promoters, acid generators, sensitizers, and quenchers may be included in the resist material.

[0084] The content of the optional components as described above is preferably 10 mass % or less, and more preferably 5 mass % or less, based on the total mass of the resist material.

[0085] (resist film) The present invention may also relate to a resist film formed from the above-mentioned resist material. The resist film is used when forming a pattern on a substrate or the like, and can function as a protective film when etching the substrate. The resist film includes a layered film before forming a pattern and an intermittent film after forming a pattern.

[0086] 1(a) shows a laminate in which a resist film 40 is formed on a substrate 10. Although not shown, another layer may be provided between the substrate 10 and the resist film 40.

[0087] 1(b), at least a portion of the resist film 40 is removed to form a pattern shape desired to be formed on the substrate 10. For example, the resist film 40 is subjected to exposure and development treatment, whereby a pattern shape as shown in FIG.

[0088] In the exposure process, the resist film 40 is irradiated with electromagnetic waves through a mask on which a circuit pattern is drawn, and the resist film in the light-irradiated portion is altered to transfer the pattern. At this time, it is preferable that the main chain of the polymer contained in the resist film is cut in the light-irradiated portion. This reduces the molecular weight of the polymer, and the exposed portion can be dissolved and removed with a developer, forming an intermittent portion of the resist film. The intermittent portion of the resist film thus formed exposes the substrate 10. The exposed substrate 10 is subjected to reactive ion etching such as inductively coupled plasma using chlorine gas, boron trichloride, tetrafluoromethane gas, trifluoromethane gas, hexafluoroethane gas, octafluoropropane gas, octafluorobutane gas, sulfur hexafluoride gas, argon gas, oxygen gas, helium gas, or the like to form a pattern on the substrate 10 as shown in FIG. 1(c). In addition, in the exposure process, exposure without using a mask such as a maskless exposure machine or an electron beam lithography device can also be performed. In this case, a latent image can be directly written on the resist film 40 by irradiating the resist film 40 with light energy using a fine beam.

[0089] The thickness of the resist film can be adjusted appropriately depending on the application, but for example, it is preferably 1 nm or more and 20,000 nm or less, more preferably 1 nm or more and 10,000 nm or less, even more preferably 1 nm or more and 5,000 nm or less, and particularly preferably 1 nm or more and 3,000 nm or less.

[0090] The resist film may be a film for introducing metal, or may be a film into which a metal has been introduced. The resist film may contain a metal. In this case, the metal content of the resist film is preferably 3 at% or more, more preferably 5 at% or more, even more preferably 7 at% or more, and particularly preferably 10 at% or more. The metal content can be calculated, for example, by the following method. The resist film after the introduction of the metal is subjected to EDX analysis (energy dispersive X-ray analysis) using an electron microscope JSM7800F (manufactured by JEOL Ltd.), and the ratio of the metal component (metal content) is calculated, which is the metal content.

[0091] (Pattern formation method) The present invention also relates to a pattern forming method using the above-mentioned resist material. Specifically, the pattern forming method preferably includes a step of applying the above-mentioned resist material onto a substrate to form a resist film, an exposure step, and a development step.

[0092] Examples of substrates used in the pattern formation method include substrates made of glass, silicon, SiN, GaN, AlN, SiO2, quartz, sapphire, etc. Substrates made of organic materials such as PET, PE, PEO, PS, cycloolefin polymer, polylactic acid, and cellulose nanofiber may also be used.

[0093] Before applying the resist material to the substrate, it is preferable to provide a process of washing the substrate. By washing the substrate surface, the coating property of the resist material is improved. As the washing treatment method, a conventionally known method can be used, for example, oxygen plasma treatment, ozone oxidation treatment, acid-alkali treatment, chemical modification treatment, etc.

[0094] The method of applying the resist material is not particularly limited, but for example, the resist material can be applied to the substrate by a known method such as spin coating. After applying the resist material, the resist material may be cured by heating to form a resist film. The temperature at which the coating film is heated is not particularly limited, but is preferably 60° C. or higher and 550° C. or lower. The heat treatment is preferably performed in the atmosphere at a relatively low temperature.

[0095] The substrate and the resist film are preferably laminated in this order so that adjacent layers are in direct contact with each other, but other layers may be provided between each layer. For example, an anchor layer or an antireflection film may be provided between the substrate and the resist film. The anchor layer is a layer that controls the wettability of the substrate and enhances the adhesion between the substrate and the resist film. The antireflection film is a layer that absorbs the electromagnetic waves used. In addition, a plurality of layers made of different materials may be sandwiched between the substrate and the resist film. These materials are not particularly specified, but examples include inorganic materials such as SiO2, SiN, Al2O3, AlN, GaN, GaAs, W, Cr, Ru, TaN, SOG, and amorphous carbon, and organic materials such as commercially available SOC and adhesives. When an antireflection film is provided between the substrate and the resist film, there is no particular restriction on the composition for the antireflection film used to form the antireflection film, and any of those commonly used in lithography processes can be selected and used.

[0096] When forming a pattern on a resist film, it is preferable to include a step of performing exposure through a mask on which a circuit pattern is drawn (exposure step), or a step of performing exposure using fine electromagnetic waves without using a mask (exposure step). The electromagnetic waves used for exposure can be KrF excimer laser (wavelength 248 nm), ArF excimer laser (wavelength 193 nm), F2 excimer laser (wavelength 157 nm), electron beam, EUV (extreme ultraviolet, wavelength 13.5 nm or less), etc. For exposure, it is preferable to use electron beam or EUV in order to draw a fine pattern. After exposure, post exposure bake can be performed as necessary. Post exposure bake is preferably performed under conditions of a heating temperature of 70°C to 150°C and a heating time of 0.3 to 10 minutes.

[0097] In the exposure process, the resist film is irradiated with electromagnetic waves to change the properties of the resist film in the areas exposed to light, thereby transferring the mask pattern. In this case, it is preferable that the main chain of the polymer contained in the resist film is cut in the areas exposed to light. In the areas where the main chain of the polymer is cut, the exposed areas of the resist film (resist material) will be removed in the subsequent development process.

[0098] When the resist film is irradiated with electromagnetic waves in the exposure step, the wavelength of the electromagnetic waves is preferably 15 nm or less, and the wavelength of the electromagnetic waves is preferably 0.0001 nm or more. By irradiating the resist film with electromagnetic waves having a wavelength of 15 nm or less in the exposure step, a fine pattern can be formed with high accuracy.

[0099] In addition, when the resist material contains a polymer having a crosslinking group or a crosslinking compound is added, the crosslinking reaction of the polymer in the exposed area can be promoted and insolubilized by irradiating the resist with light energy. In this case, the resist film (resist material) in the unexposed area can be removed by treating the resist with an appropriate developer.

[0100] The developer used in the development step is not particularly limited, but a known developer can be used. For example, examples include aromatics such as xylene, toluene, and anisole; esters such as pentyl acetate, hexyl acetate, heptyl acetate, octyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, ethyl lactate, propyl lactate, butyl lactate, and γ-butyrolactone; alcohols such as ethanol and isopropanol; ketones such as diethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as diethylene glycol dimethyl ether; organic acids such as acetic anhydride and acetic acid; aqueous solutions of alkali metal hydroxides such as potassium hydroxide and sodium hydroxide; aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine. As the developer, these can be used alone or in combination of two or more. Furthermore, surfactants and the like can be added to these developers. The development conditions are appropriately selected from a temperature of -70 to 50° C. and a time of 10 to 300 seconds.

[0101] Among them, the developer used in the development step preferably contains at least one selected from the group consisting of ester compounds, ketone compounds, and alcohol compounds. By using such a developer, high sensitivity and high-definition patterning can be easily performed. The developer may be a combination of two or more of the above-mentioned compounds. For example, when the above-mentioned compounds are mixed, the developer may be a mixture of two or more ester compounds such as butyl acetate, a mixture of an ester compound and an alcohol compound such as isopropyl alcohol, a mixture of an ester compound and a ketone compound such as cyclohexanone, a mixture of an ester compound and an ether compound such as diethylene glycol dimethyl ether, a mixture of two or more ketone compounds, a mixture of a ketone compound and an alcohol compound, a mixture of a ketone compound and an ether compound, a mixture of two or more alcohol compounds, a mixture of an alcohol compound and an organic acid such as acetic anhydride, a mixture of an alcohol compound and an amine compound such as tetramethylammonium hydroxide, or the like.

[0102] In addition, a rinsing step using a rinsing liquid may be performed after the development step. The rinsing liquid is not particularly limited, but any known rinsing liquid may be used. For example, xylene, butyl acetate, ethanol, isopropyl alcohol, methyl isobutyl ketone, pure water, etc. may be used. As the rinsing liquid, each of these may be used alone or in combination of two or more. Furthermore, a surfactant may be added to these rinsing liquids. The conditions for the rinsing step are appropriately selected from a temperature of -70 to 50°C and a time of 10 to 100 seconds.

[0103] The pattern forming method of the present invention may further include a metal introduction step before the development step. That is, the pattern forming method of the present invention may further include a metal introduction step between the step of forming a resist film and the exposure step, or after the development step. In this case, the metal introduction step may include a step of introducing a metal into a resist film, such as the SIS method (Sequential Infiltration Synthesis). Examples of the metal to be introduced include Li, Be, Na, Mg, Al, Si, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Rb, Sr, Y, Zr, Nb, Mo, Ru, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, La, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Tl, Pb, Bi, Po, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. Such a process can be carried out by, for example, the method described in Journal of Photopolymer Science and Technology Volume 29, Number 5 (2016) 653-657. In addition, in the step of introducing the metal, a method of using a metal complex gas, a method of applying a solution containing the metal, or a method of introducing the metal into the resist by an ion implant method can be adopted.

[0104] The pattern forming method of the present embodiment is a method for forming a pattern on a resist film formed from a resist material, but may further include a step of processing a semiconductor substrate or the like using the pattern formed on the resist film as a protective film. Such a step is called an etching step. In this case, the etching step is provided as a post-step of the developing step.

[0105] Examples of methods for processing the semiconductor substrate in the etching step include known methods such as reactive ion etching (RIE) such as chemical dry etching, chemical wet etching (wet development), sputter etching, physical etching such as ion beam etching, etc. The processing of the semiconductor substrate is preferably performed by dry etching using a gas such as tetrafluoromethane, perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, chlorine, sulfur hexafluoride, difluoromethane, nitrogen trifluoride, and chlorine trifluoride. EXAMPLES

[0106] The features of the present invention will be explained in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. Note that n, m, l, and s in the structural formulas in the following examples respectively represent the number of repetitions of each structural unit in the polymer.

[0107] [Example 1: Synthesis of copolymer 1] (Synthesis of acetyl sugar methacrylate 1) 20 g of xylose was added to a mixed solution of 250 g of acetic anhydride (FUJIFILM Wako Pure Chemical Industries, Ltd.) and 320 g of acetic acid (FUJIFILM Wako Pure Chemical Industries, Ltd.), and stirred at 30°C for 2 hours. Approximately 5 times the amount of cold water as the solution was slowly added while stirring, and after stirring for 2 hours, it was left to stand overnight to precipitate crystals. 10 g of precipitated crystals were added to a solution of 400 mL of tetrahydrofuran (THF, FUJIFILM Wako Pure Chemical Industries, Ltd.) in a flask, 1.2 g of ethylenediamine (FUJIFILM Wako Pure Chemical Industries, Ltd.) and 0.14 g of acetic acid, and the solution was cooled to 0°C, and stirred for 4 hours. This was poured into 1 L of cold water and extracted twice with dichloromethane (FUJIFILM Wako Pure Chemical Industries, Ltd.). 20 g of this extract, 300 mL of dichloromethane, and 4.8 g of triethylamine (Tokyo Chemical Industry Co., Ltd.) were placed in a flask and cooled to -30°C. 2.8 g of methacryloyl chloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added and stirred for 2 hours. This was poured into 300 mL of cold water, extracted twice with dichloromethane, and the solvent was concentrated to obtain 16.1 g of acetyl sugar methacrylate 1. The structure of the obtained acetyl sugar methacrylate 1 is as follows. [ka]

[0108] (Synthesis of acetyl sugar methacrylate 1-trifluoroethyl methacrylate random copolymer) After placing 19.5g of acetyl sugar methacrylate 1 and 0.5g of 2,2,2-trifluoroethyl methacrylate (Tokyo Chemical Industry Co., Ltd.) in a flask, 100g of THF as a solvent and 0.8g of azobisisobutyronitrile (Tokyo Chemical Industry Co., Ltd.) as a polymerization initiator were placed in the flask, and the flask was sealed and replaced with nitrogen. The temperature was raised to 78°C under a nitrogen atmosphere and stirred for 6 hours. Then, the temperature was returned to room temperature and the flask was placed under air. 300g of methanol (Fujifilm Wako Pure Chemical Industries, Ltd.) was dropped into the obtained solution to precipitate a polymer. Then, the solution containing the precipitated polymer was suction filtered to obtain 11g of white copolymer 1. The structure of each structural unit of the obtained copolymer 1 is as follows. [ka]

[0109] [Example 2: Synthesis of copolymer 2] (Synthesis of acetyl sugar methacrylate 1-methyl chloroacrylate-trifluoroethyl methacrylate random copolymer) After adding 14.7g of acetyl sugar methacrylate 1, 4.6g of methyl 2-chloroacrylate (Tokyo Chemical Industry Co., Ltd.) and 0.7g of 2,2,2-trifluoroethyl methacrylate to the flask, 100g of THF as a solvent and 0.8g of azobisisobutyronitrile as a polymerization initiator were added, and the flask was sealed and replaced with nitrogen. The temperature was raised to 78°C under a nitrogen atmosphere and stirred for 6 hours. Then, the temperature was returned to room temperature, the flask was placed under air, and 300g of methanol was dropped into the obtained solution to precipitate a polymer. Then, the solution containing the precipitated polymer was suction filtered to obtain 12.1g of white copolymer 2. The structure of each structural unit of the obtained copolymer 2 is as follows. [ka]

[0110] [Example 3: Synthesis of copolymer 3] (Synthesis of acetyl sugar methacrylate 1-methyl methacrylate-styrene-trifluoroethyl methacrylate random copolymer) After placing 11.6g of acetyl sugar methacrylate 1, 3.4g of methyl methacrylate (Tokyo Chemical Industry Co., Ltd.), 4.2g of styrene (Tokyo Chemical Industry Co., Ltd.), and 0.9g of 2,2,2-trifluoroethyl methacrylate in a flask, 100g of THF as a solvent and 0.8g of azobisisobutyronitrile as a polymerization initiator were placed in the flask, and the flask was sealed and replaced with nitrogen. The temperature was raised to 78°C under a nitrogen atmosphere and stirred for 6 hours. After that, the temperature was returned to room temperature, the flask was placed under air, and 310g of methanol was dropped into the obtained solution to precipitate a polymer. Then, the solution containing the precipitated polymer was suction filtered to obtain 10.2g of white copolymer 3. The structure of each structural unit of the obtained copolymer 3 is as follows. [ka]

[0111] [Example 4: Synthesis of copolymer 4] (Synthesis of acetyl sugar chloroacrylate) In the synthesis of acetyl sugar methacrylate 1, methacryloyl chloride was replaced with 2-chloroacrylic acid chloride (manufactured by 1Click Chemistry Stock Products), and 20 g of acetyl sugar chloroacrylate was obtained. The structure of the obtained acetyl sugar chloroacrylate is as follows. [ka]

[0112] (Synthesis of acetyl sugar chloroacrylate-methyl chloroacrylate-methylstyrene-trifluoroethyl methacrylate random copolymer) In the synthesis of copolymer 3, 11.6g of acetyl sugar methacrylate 1 was changed to 9.8g of acetyl sugar chloroacrylate, 3.4g of methyl methacrylate was changed to 3.9g of 2-methyl chloroacrylate, 4.2g of styrene was changed to 4.6g of α-methylstyrene (Tokyo Chemical Industry Co., Ltd.), and the amount of 2,2,2-trifluoroethyl methacrylate added was changed from 0.9g to 1.8g. The same method was used to obtain copolymer 4 (9.7g). The structures of the respective structural units of the obtained copolymer 4 are as follows: [ka]

[0113] [Example 5: Synthesis of copolymer 5] (Synthesis of propyl sugar methacrylate) In the synthesis of acetyl sugar methacrylate 1, the mixed solution of 250g of acetic anhydride and 320g of acetic acid was changed to 300g of propionic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) and 400g of propionic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 22.1g of propyl sugar methacrylate was obtained. The structure of the obtained propyl sugar methacrylate is as follows. [ka]

[0114] (Synthesis of Propyl Sugar Methacrylate-Methyl Chloroacrylate-Methylstyrene-Trifluoroethyl Methacrylate Random Copolymer) In the synthesis of copolymer 3, 11.6g of acetyl methacrylate 1 was changed to 8.1g of propyl methacrylate, 3.4g of methyl methacrylate was changed to 2.5g of 2-chloromethyl acrylate, 4.2g of styrene was changed to 3.6g of α-methylstyrene, and the amount of 2,2,2-trifluoroethyl methacrylate added was changed from 0.9g to 6.2g, but the same method was used to obtain copolymer 5 (10.0g). The structure of each structural unit of the obtained copolymer 5 is as follows: [ka]

[0115] [Example 6: Synthesis of copolymer 6] (Synthesis of trifluoroacetyl sugar methacrylate) In the synthesis of acetyl sugar methacrylate 1, the mixed solution of 250g of acetic anhydride and 320g of acetic acid was changed to 400g of trifluoroacetic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) and 500g of trifluoroacetic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), and 20.0g of trifluoroacetyl sugar methacrylate was obtained. The structure of the obtained trifluoroacetyl sugar methacrylate is as follows. [ka]

[0116] (Synthesis of trifluoroacetyl sugar methacrylate-methyl chloroacrylate-methylstyrene-trifluoroethyl methacrylate random copolymer) In the synthesis of copolymer 3, 11.6g of acetyl sugar methacrylate 1 was changed to 11.9g of trifluoroacetyl sugar methacrylate, 3.4g of methyl methacrylate was changed to 3.4g of 2-chloromethyl acrylate, 4.2g of styrene was changed to 4.0g of α-methylstyrene, and 0.9g of 2,2,2-trifluoroethyl methacrylate was changed to 0.8g. Except for this, copolymer 6 was obtained in the same manner as above. The structure of each structural unit of the obtained copolymer 6 is as follows: [ka]

[0117] [Example 7: Synthesis of copolymer 7] (Synthesis of sugar methacrylate) 33 g of xylose was dissolved in 150 mL of water, and 28.5 g of ammonium hydrogen carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added 4 times every 24 hours, and the mixture was stirred at 37°C for 96 hours. Then, 200 mL of distilled water was added, and water was distilled off until the volume was 20 mL, after which 150 mL of water was added and the mixture was concentrated until the volume was 10 mL. This was repeated until the ammonia odor disappeared, and after freeze-drying, a white solid was obtained. This substance was dissolved in 1x10 -3 M was dissolved in 50 mL of KOH (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.), 10.4 g of 2-isocyanate ethyl methacrylate (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) was added, and the mixture was vigorously stirred for 12 hours while maintaining the temperature at 3°C. After removing the precipitated white solid, the filtrate was washed four times with 50 mL of diethyl ether (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) and freeze-dried. After this, the obtained white solid was dissolved in a mixed solution of 2 mL of water and 10 mL of methanol, dropped into a mixed solution of 200 mL of acetone (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) and cooled. Then, the mixture was filtered and dried under reduced pressure to obtain 25 g of sugar methacrylate. The structure of sugar methacrylate is as follows. [ka]

[0118] (Synthesis of sugar methacrylate-methyl chloroacrylate-methylstyrene-trifluoroethyl methacrylate random copolymer) In the synthesis of copolymer 3, 11.6g of acetyl sugar methacrylate 1 was changed to 14.2g of sugar methacrylate, 3.4g of methyl methacrylate was changed to 2.2g of 2-chloromethyl acrylate, 4.2g of styrene was changed to 2.8g of α-methylstyrene, and the amount of 2,2,2-trifluoroethyl methacrylate added was changed from 0.9g to 0.8g, but the same method was used to obtain copolymer 7 (11.3g). The structure of each structural unit of the obtained copolymer 7 is as follows. [ka]

[0119] [Example 8: Synthesis of copolymer 8] (Synthesis of Acetyl Xylooligosaccharide Methacrylate) The synthesis was carried out in the same manner as in the synthesis of acetyl sugar methacrylate 1, except that 20 g of xylose was replaced with 55 g of xylooligosaccharide (average sugar chain length 3), to obtain 30.0 g of acetyl xylooligosaccharide methacrylate. The structure of the obtained acetyl xylooligosaccharide methacrylate is as follows. [ka]

[0120] (Synthesis of Acetyl Xylooligosaccharide Methacrylate-Methyl Chloroacrylate-Methylstyrene-Bromoethyl Acrylate Random Copolymer) In the synthesis of copolymer 3, 11.6g of acetyl sugar methacrylate 1 was changed to 14.6g of acetyl xylooligosaccharide methacrylate, 3.4g of methyl methacrylate was changed to 2.3g of 2-chloromethyl acrylate, 4.2g of styrene was changed to 2.6g of α-methylstyrene, and 0.9g of 2,2,2-trifluoroethyl methacrylate was changed to 0.6g of 2-bromoethyl acrylate (manufactured by Alfa Aesar). The structure of each structural unit of the obtained copolymer 8 is as follows. [ka]

[0121] [Example 9: Synthesis of copolymer 9] (Synthesis of acetyl sugar methacrylate 2) 120g of acetic anhydride was added to 10g of sugar methacrylate and stirred for 2 hours. After that, the reaction was stopped with a 33% by mass solution of magnesium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and pure water was added to precipitate crystals, thereby obtaining 11g of acetyl sugar methacrylate 2. The structure of the obtained acetyl sugar methacrylate 2 is as follows. [ka]

[0122] (Synthesis of acetyl sugar methacrylate 2-methyl chloroacrylate-methylstyrene-2,2,3,3,3-pentafluoropropyl methacrylate random copolymer) In the synthesis of copolymer 3, 11.6g of acetyl sugar methacrylate 1 was changed to 11.9g of acetyl sugar methacrylate 2, 3.4g of methyl methacrylate was changed to 3.3g of 2-chloromethyl acrylate, 4.2g of styrene was changed to 3.9g of α-methylstyrene, and 0.9g of 2,2,2-trifluoroethyl methacrylate was changed to 1.0g of 2,2,3,3,3-pentafluoropropyl methacrylate (Sigma-Aldrich Co.), but the same method was used to obtain copolymer 9 (10.5g). The structures of the respective structural units of the obtained copolymer 9 are as follows: [ka]

[0123] [Example 10: Synthesis of copolymer 10] (Synthesis of acetyl sugar methacrylate 1-methyl chloroacrylate-methylstyrene-trifluoroethyl methacrylate random copolymer) In the synthesis of copolymer 3, the amount of acetyl sugar methacrylate 1 was changed from 11.6 g to 10.9 g, methyl methacrylate was changed from 3.4 g to 3.8 g of 2-chloromethyl acrylate, and styrene was changed from 4.2 g to 4.5 g of α-methylstyrene, but the same method was used to obtain copolymer 10 (10.7 g). The structure of each structural unit of the obtained copolymer 10 is as follows. [ka]

[0124] [Example 11: Synthesis of copolymer 11] (Synthesis of acetyl sugar methacrylate 1-methyl chloroacrylate-methylstyrene-trichloroethyl acrylate random copolymer) In the synthesis of copolymer 3, the amount of acetyl sugar methacrylate 1 added was changed from 11.6g to 11.1g, 3.4g of methyl methacrylate was changed to 3.9g of 2-chloromethyl acrylate, 4.2g of styrene was changed to 4.0g of α-methylstyrene, and 0.9g of 2,2,2-trifluoroethyl methacrylate was changed to 1.1g of 2,2,2-trichloroethyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), but 6.1g of copolymer 11 was obtained in the same manner. The structure of each structural unit of the obtained copolymer 11 is as follows. [ka]

[0125] [Example 12: Synthesis of copolymer 12] (Synthesis of acetyl sugar methacrylate 1-methyl fluoroacrylate-methylstyrene-trifluoroethyl methacrylate random copolymer) In the synthesis of copolymer 3, the amount of acetyl sugar methacrylate 1 added was changed from 11.6 g to 11.2 g, methyl methacrylate 3.4 g was changed to 2-fluoromethyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 3.4 g, and styrene 4.2 g was changed to α-methylstyrene 4.6 g, but the same method was used to obtain copolymer 12 11.0 g. The structure of each constituent unit of the obtained copolymer 12 is as follows. [ka]

[0126] [Example 13: Synthesis of copolymer 13] (Synthesis of acetylated sugar styrene) 20 g of xylose was added to a mixed solution of 250 g of acetic anhydride (FUJIFILM Wako Pure Chemical Industries, Ltd.) and 320 g of acetic acid (FUJIFILM Wako Pure Chemical Industries, Ltd.), and stirred at 30°C for 2 hours. Approximately 5 times the amount of cold water as the solution was slowly added while stirring, and after stirring for 2 hours, the solution was left to stand overnight to precipitate crystals, and the crystals were filtered to synthesize 30 g of acetyl sugar. 10.8 g (90 mmol) of acetyl sugar 4-vinylphenol (FUJIFILM Wako Pure Chemical Industries, Ltd.), 32.2 g (32 mmol) of acetyl sugar, and 0.5 g of zinc chloride (FUJIFILM Wako Pure Chemical Industries, Ltd.) were heated at 160°C for 30 minutes in a silicon oil bath while stirring. The molten mixture was cooled to about 60°C and dissolved in 200 mL of benzene (FUJIFILM Wako Pure Chemical Industries, Ltd.). This solution was washed twice with water, then with 1M sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) until the aqueous phase was almost colorless. It was then washed twice with water, dried, and concentrated under reduced pressure to obtain 26.5 g of acetyl-sugarstyrene. The structure of the obtained acetyl-sugarstyrene is as follows: [ka]

[0127] (Synthesis of acetylated styrene-methyl chloroacrylate-methylstyrene-trifluoroethyl methacrylate random copolymer) In the synthesis of copolymer 3, 11.6g of acetyl sugar methacrylate 1 was changed to 11.2g of acetyl sugar styrene, 3.4g of methyl methacrylate was changed to 3.7g of methyl 2-chloroacrylate, and 4.2g of styrene was changed to 4.3g of α-methylstyrene, but the same method was used to obtain copolymer 13 (10.8g). The structure of each structural unit of the obtained copolymer 13 is as follows. [ka]

[0128] [Comparative Example 1: Synthesis of Copolymer 14] (Synthesis of methyl chloroacrylate-methylstyrene-trifluoromethyl methacrylate random copolymer) 10.0g of α-methylstyrene, 8.9g of methyl 2-chloroacrylate, and 1.4g of 2,2,2-trifluoroethyl methacrylate were placed in a flask, followed by 100g of THF as a solvent and 0.8g of azobisisobutyronitrile as a polymerization initiator, and then the flask was sealed and replaced with nitrogen. The temperature was raised to 78°C under a nitrogen atmosphere and stirred for 6 hours. Then, the temperature was returned to room temperature, the flask was placed under air, and 300g of methanol was dropped into the obtained solution to precipitate a polymer. Then, the solution containing the precipitated polymer was suction filtered to obtain 14.0g of white copolymer 14. The structure of each structural unit of the obtained copolymer 14 is as follows. [ka]

[0129] [Comparative Example 2: Synthesis of Copolymer 15] (Synthesis of acetyl sugar methacrylate 1-methyl chloroacrylate-methylstyrene random copolymer) In the synthesis of copolymer 2, the amount of acetyl sugar methacrylate 1 was changed from 14.7g to 11.1g, the amount of 2-methyl chloroacrylate was changed from 4.6g to 4.5g, and 4.4g of α-methylstyrene was added instead of 2,2,2-trifluoroethyl methacrylate. The copolymer 15 was obtained in a similar manner, with the exception of this. The structure of each structural unit of the obtained copolymer 15 is as follows: [ka]

[0130] [Comparative Example 3: Synthesis of copolymer 16] (Synthesis of acetyl sugar methacrylate-methyl chloroacrylate random copolymer) Copolymer 16 (10.5 g) was obtained in the same manner as in the synthesis of copolymer 1, except that the amount of acetyl sugar methacrylate 1 was changed from 19.5 g to 14.8 g, and 5.2 g of methyl 2-chloroacrylate was added instead of 0.5 g of 2,2,2-trifluoroethyl methacrylate. The structure of each constituent unit of the obtained copolymer 16 is as follows. [ka]

[0131] [Comparative Example 4: Synthesis of copolymer 17] (Synthesis of Adamantyl Methacrylate-Methyl Chloroacrylate-Methylstyrene-Trifluoroethyl Methacrylate Random Copolymer) In the synthesis of copolymer 3, 11.6g of acetyl methacrylate 1 was changed to 8.7g of 1-adamantyl methacrylate (Tokyo Chemical Industry Co., Ltd.), 3.4g of methyl methacrylate was changed to 4.7g of 2-chloromethyl acrylate, 4.2g of styrene was changed to 5.6g of α-methylstyrene, and the amount of 2,2,2-trifluoroethyl methacrylate added was changed from 0.9g to 1.1g, but the same method was used to obtain copolymer 17 (8.4g). The structures of the respective structural units of the obtained copolymer 17 are as follows: [ka]

[0132] [Comparative Example 5: Synthesis of Copolymer 18] (Synthesis of acetyl sugar methacrylate-methyl methacrylate-methylstyrene random copolymer) In the synthesis of copolymer 2, the amount of acetyl methacrylate 1 was changed from 14.7g to 11.5g, methyl 2-chloroacrylate was changed from 4.6g to 3.9g of methyl methacrylate, and α-methylstyrene was added instead of 0.7g of 2,2-trifluoroethyl methacrylate, to obtain 9.8g of copolymer 18 in the same manner. The structure of each structural unit of the obtained copolymer 18 is as follows: [ka]

[0133] [Analysis of copolymers] <Weight average molecular weight> The weight average molecular weight of the copolymer was measured by gel permeation chromatography (GPC). GPC column: Shodex K-806M / K-802 connected column (Showa Denko) Column temperature: 40℃ Mobile phase: Chloroform Detector: RI After the polymerization was completed, the degree of polymerization was confirmed by GPC to confirm that random copolymers with the desired degree of polymerization and average molecular weight were produced. The number-average molecular weight Mn of each copolymer was 50,000.

[0134] <Ratio of unit (a):unit (b):unit (c):unit (d)> The ratio of each unit of the copolymer was measured using JNM-ECS-400 (manufactured by JEOL Ltd.). 1 The calculation was performed by measuring H-NMR. The ratio (molar ratio) of the copolymer's units (a), (b), (c), and (d) was calculated from the peak area derived from each unit. The molar ratio indicates the ratio of the number of each unit present in the copolymer.

[0135] [Table 1]

[0136] [Evaluation of copolymer solubility] The synthesized copolymer was weighed and dissolved in propylene glycol monomethyl ether acetate (Kanto Chemical) at 23° C. to a concentration of 3.0% by mass. The solubility was confirmed visually and evaluated according to the following criteria. ○: The solution is clear and there is no cloudiness or precipitation. △: The solution is cloudy, but there is no precipitate. ×: Precipitation is observed in the solution

[0137] [Preparation of resist evaluation samples] The synthesized copolymer was weighed and dissolved in propylene glycol monomethyl ether acetate (Kanto Chemical) at 23°C to a concentration of 3.0% by mass. This solution was spin-coated onto a silicon wafer to a thickness of 100 nm, and then heated on a hot plate at 180°C for 2 minutes to be baked. The baked silicon wafer was irradiated with an electron beam using an electron beam lithography device ELS-F125 (Elionix) under conditions of an acceleration voltage of 50 kV and a current of 500 pA (wavelength of 0.0053 nm) to draw a latent image. Thereafter, the steps shown below were carried out to prepare a sample for evaluating sensitivity and resolution, and the sensitivity was evaluated.

[0138] [Sensitivity evaluation] The dose was 15 μC / cm 2 , 30μC / cm 2 , 45μC / cm 2 , 60μC / cm 2 , 160μC / cm 2 A latent image of a line and space with a line width of 100 nm and a line:space ratio of 1:1 was drawn on the resist film. The silicon wafer after drawing was immersed in pentyl acetate (Tokyo Chemical Industry Co., Ltd.) at 23°C for development. After development, the wafer was dried with nitrogen blow to prepare a sample for sensitivity evaluation. The surface and cross section of the line and space portion were observed using a scanning electron microscope (SEM) JSM7800F (manufactured by JEOL Ltd.) under conditions of an acceleration voltage of 5 kV, an emission current of 86.0 μA, and a magnification of 100,000 times to confirm the sensitivity. The condition was evaluated according to the following evaluation criteria. 2 When a line and space pattern was developed at the following dose amounts, the sensitivity was evaluated as good. ○: Line and space pattern is developed ×: Line and space pattern not developed

[0139] [Table 2]

[0140] When the copolymer obtained in each of the Examples was used to form a resist film, the resist film had high sensitivity. [Explanation of symbols]

[0141] 10 Substrate 40 Resist film

Claims

1. A main chain scission resist material containing a polymer including a unit derived from a structure represented by the following general formula (101) and a unit derived from a structure represented by the following general formula (104): 【Chemistry 1】 【Chemistry 2】 In general formula (101), R 1 each independently represents a hydrogen atom, an optionally substituted alkyl group, an optionally substituted acyl group, an optionally substituted allyl group, an optionally substituted alkoxy group, or an optionally substituted alkylsilyl group, 1 may be the same or different; R 11 represents a hydrogen atom or an alkyl group which may have a substituent; R 2 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 1 represents a single bond or a linking group; In general formula (104), X 3 represents a halogenated alkyl group having 1 to 5 carbon atoms; R 5 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 4 represents a single bond or an alkylene group.

2. The main chain scission resist material according to claim 1 , wherein the polymer further comprises a unit derived from a structure represented by the following general formula (102): 【Chemistry 3】 In general formula (102), X 1 represents an optionally substituted alkyl group (excluding those containing a halogen atom as a substituent), an optionally substituted acyl group, or an optionally substituted allyl group; R 3 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 2 represents a single bond or a linking group.

3. The main chain cleavage resist material according to claim 1 or 2, wherein the polymer further comprises a unit derived from a structure represented by the following general formula (103): 【Chemistry 4】 In general formula (103), X 2 represents an aryl group which may have a substituent; R 4 represents a hydrogen atom, an alkyl group, a fluorine atom, a chlorine atom, a bromine atom or a halogenated alkyl group; Y 3 represents a single bond or a linking group.

4. The main chain cleavage resist material according to any one of claims 1 to 3, wherein the content of the unit derived from the structure represented by the general formula (104) in the polymer is 1 to 40 mol %.

5. In the general formula (101), R 2 The main chain scission resist material according to any one of claims 1 to 4, wherein is a fluorine atom, a chlorine atom, or a bromine atom.

6. In the general formula (101), R 11 The main chain scission type resist material according to any one of claims 1 to 5, wherein

7. In the general formula (102), R 3 The main chain scission resist material according to any one of claims 2 to 6, wherein is a fluorine atom, a chlorine atom, or a bromine atom.

8. A resist film formed from the main chain scission type resist material according to any one of claims 1 to 7.

9. A step of applying the main chain cleavage type resist material according to any one of claims 1 to 7 onto a substrate to form a resist film; An exposure process; A developing step.

10. The pattern forming method according to claim 9 , further comprising a metal introducing step prior to the developing step.

11. 11. The pattern forming method according to claim 9, wherein in the exposure step, the resist film is irradiated with electromagnetic waves having a wavelength of 15 nm or less.

12. The pattern formation method according to any one of claims 9 to 11, wherein the developer used in the developing step contains at least one selected from the group consisting of an ester-based compound, a ketone-based compound, and an alcohol-based compound.

Citation Information

Patent Citations

  • Formation pattern

    JP1985117243A

  • Electron beam positive resist

    JP1988137227A

  • Radiation sensitive material and pattern forming method

    JP1995234511A

  • Polymer compound, resist material and pattern forming method

    JP2002155118A

  • PURIFIED METHYL $g(a)-CHLOROACRYLATE / $g(a)-METHYLSTYRENE COPOLYMER AND ELECTRON BEAM RESIST COMPOSITION CONTAINING THE SAME

    WO1999062964A1